Rethinking health care financing models: the case of Zimbabwe's health sector - Mutopo, Yvonne (Research of GSB, 2018)
The purpose of the current study was to assess how RBF performed in terms of efficiency, effectiveness, equity and governance in the Zimbabwean context. It outlines the evolution of health systems thinking and health funding models over time to show the history and changing landscape of health care financing and their actors. General consensus is there is need to focus on results of health care investments against a background of prodigious amounts of foreign aid with marginal or no improvements in heath care delivery for decades of development assistance in developing countries. Health systems in developing countries are beset with burgeoning domestic and foreign debts as well as diminishing fiscal space that has more often put the primary health delivery system in developing nations in "comatose". The research made use of both qualitative and quantitative dimensions. Findings indicate that the pre-RBF era was characterised by poor primary health outcomes, unsound governance and a lack of confidence in the public health delivery system. However, since RBF implementation, access to health care by marginalised groups has increased, with incentives and community participation liberalising health systems to greater efficiency as shown by slight increases in post-natal care visits in rural health care centres. A trade-off between achieving efficiency and equity was found especially when scaling up health programmes under the RBF initiative. Through embracing RBF, the primary health delivery system is poised for future development attributed to community buy-in and people-centric empowerment approaches.